2023
DOI: 10.3389/fevo.2023.1284482
|View full text |Cite
|
Sign up to set email alerts
|

Significant floral changes across the Permian-Triassic and Triassic-Jurassic transitions induced by widespread wildfires

Peixin Zhang,
Minfang Yang,
Zhongfeng Jiang
et al.

Abstract: Wildfires are a major source of perturbations to the Earth’s system and have important implications for understanding long-term interactions between the global environment, climate, and organisms. In this study, current evidence for global warming, wildfires, and floral changes across the Permian-Triassic (P-T) and Triassic-Jurassic (T-J) transitions were reviewed, and their relationships were discussed. Available evidence suggests that global plant community turnover and the decline in plant diversity across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(155 reference statements)
0
2
0
Order By: Relevance
“…Palynological and charcoal data (Zhang et al, 2022; sampling locations are shown in Figure 2) were re-analyzed using new method (see below) from the Anyao Formation of the ZJ-1 borehole (35.07001°N, 112.47338°E) in the Jiyuan Basin (Figures 1A, B). Variations in spore and pollen compositions through the studied strata were used to reconstruct climatic conditions based on the climatic preferences of the parent plants (e.g., Li et al, 2020;Zhang et al, 2022;Zhang et al, 2023a;Zhang et al, 2023b;Zhang et al, 2023c). To reveal detailed changes in climatic conditions and plant diversity in the study area, we undertook non-metric multidimensional scaling ordination analysis (nMDS) and Simpson (1-D) Diversity Index analysis based on palynological fossils (e.g., Slater et al, 2019;Zhang et al, 2023b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palynological and charcoal data (Zhang et al, 2022; sampling locations are shown in Figure 2) were re-analyzed using new method (see below) from the Anyao Formation of the ZJ-1 borehole (35.07001°N, 112.47338°E) in the Jiyuan Basin (Figures 1A, B). Variations in spore and pollen compositions through the studied strata were used to reconstruct climatic conditions based on the climatic preferences of the parent plants (e.g., Li et al, 2020;Zhang et al, 2022;Zhang et al, 2023a;Zhang et al, 2023b;Zhang et al, 2023c). To reveal detailed changes in climatic conditions and plant diversity in the study area, we undertook non-metric multidimensional scaling ordination analysis (nMDS) and Simpson (1-D) Diversity Index analysis based on palynological fossils (e.g., Slater et al, 2019;Zhang et al, 2023b).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of global warming climatic conditions, in higher temperatures lightning becomes more frequent and wildfires can be more destructive (Glasspool et al, 2015;Miller and Baranyi, 2021). As lightning is the main cause of wildfire, higher temperatures associated with CAMP volcanism would be expected to have increased the frequency and destructiveness of wildfire events (e.g., van de Schootbrugge et al, 2008;Belcher et al, 2010;Glasspool et al, 2015;Lu et al, 2020;Lu et al, 2022;Zhang et al, 2022;Zhang et al, 2023a;Zhang et al, 2023c). Wildfires are influenced by a variety of factors, including the supply of combustible material, oxygen concentration required for combustion, a conducive climate with low moisture, and an ignition mechanism (Scott, 2000;Glasspool et al, 2015;Lu et al, 2020;Zhang et al, 2022).…”
Section: Camp As a Potential Driver Of The Triassic-jurassic Transiti...mentioning
confidence: 99%